The Study of Personality Profile of Distance Education Teacher - Ирина Александровна Бакаева; Людмила Николаевна Ванжа (Rossijskij psihologičeskij žurnal., 2015)
The article analyzes the results of an empirical study on the attitude of distance education teachers to independent activity of students. In the course of study teachers were divided into groups according to the criteria of their attitude to independent activity of students, which they expressed in questionnaires. Using content analysis groups were identiWed according to cognitive, emotional, behavioral criteria. The study exposed such areas as life-purpose orientations, self-attitude and self-esteem, interpersonal relationships. The article presents key results of the study, characteristics of diXerent personality spheres of distance education teachers with varying degrees of competence and effectiveness in distance education. The article draws conclusions about the proneness of a certain type of teacher’s personality to use technologies of initiating independent activity, in particular distance technology. It is concluded that distance education teachers are divided into more competent in matters of technologies of initiating independent activity of students, and less competent. It is emphasized that the respondents have diXerent levels of systematic use of independent activity technologies in their practice, which aXects the overall eXectiveness, particularly the integrity of students. It describes features of life-purpose orientations, which are manifested in generally high meaningfulness of life, expressed internal locus of control. The article presents general patterns of personality proWles of all distance education teachers, such as positive self-attitude, the average for the factor of personal strength, value and low activity; teachers demonstrate predominant focus on the task and low rate on the scale of “sociability”. The article also describes signiWcant diXerences in such qualities, as: exactingness, discipline, strong will, energy. Theoretical and empirical Wndings substantiate the idea that the distance education teacher demonstrates a certain type of personality, and more eXective in this Weld teachers express these personality traits more clearly, which supposedly justiWes their choice of the distance form of work with students.